Influencia de los materiales de cementación en la distribución de los esfuerzos en un incisivo central superior rehabilitado con poste. Análisis de elementos finitos (2011)
ABSTRACT: In order to improve predictability of dental restorations, new cement materials with different mechanical and physical properties are frequently developed. The purpose of this study was to evaluate and analyze the influence of cement materials in the distribution of stresses in an upper central incisor restored with a cast intrarradicular retention element and two prefabricated elements using the finite element method (FEM). Methods: a modeled upper central incisor restored with three dowels (based metal cast post, titanium prefabricated post and fiber glass) and each one cemented with resin-modified glass ionomer luting cement, self-adhesive resin luting cement and dual cured adhesive resin. The variables included were modulus of elasticity and Poisson’s ratio for all the components of the model. Von Misses stresses, main maximum and main minimum as well as maximum shear stress were calculated for each model. Results: the finite element analysis indicated that the cement influences stress distribution when the post is more flexible as in the case of prefabricated fiberglass because both post and cement receive the stress altogether. Conclusions: as the modulus of elasticity of luting cement is higher, the stress received among them increases, but its influence in the system depends on other variables such as the type of post that was used.